PENGUATAN METODE MUBASYAROH TERHADAP PEMBELAJARAN KOSA KATA BAHASA ARAB DI LEMBAGA KELOMPOK STUDI KHUSUS (KSK) FATHIMATUZZAHRO’ PAITON PROBOLINGGO - Adawiyah, Yayah Robiatul; Firdaus, Sulton; Istibsyaroh, Istibsyaroh (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
This study aims to determine the strengthening of the direct method in learning Arabic vocabulary in the special study group fathimatuzzahro'. The direct method or in Arabic called thoriqoh mubasyaroh is a method used by a teacher to present learning Arabic vocabulary by using a direct introduction to Arabic. The essence of language itself is to speak or speak, so the purpose of learning Arabic vocabulary is that apart from knowing the rules, we are also able to speak. Students are expected not only to master the rules in learning Arabic vocabulary but also to be able to speak the Arabic language that has been studied. With the direct method, students will be tsaught little by little and will be taught by the teacher a habituation in Arabic. In principle, the direct method is very important for students in learning Arabic vocabulary because it will train their language skills in speaking Arabic. This study uses a descriptive research model with a case study method which is a qualitative research. This means that information from various sources/informants is presented in the form of words and language in a special natural context. With this method, students will find it easy topronounce Arabic vocabulary using good lahjah.